RIAS KARAKTER TOKOH NYI MISNI DALAM FILM PEREMPUAN TANAH JAHANAM - Priyanti, Adinda Puspa; Indriani, Sri Seti; Rosfiantika, Evi (Universitas Swadaya Gunung Jati, 2024)
In a film, meanings often emerge and are usually implicit. The meaning conveyed can be through the cast's conversations, the background of the filming, and even the cast's makeup. The abstract meaning that emerges from the elements in the film encourages researchers to analyze the makeup of the characters in the movie 'Perempuan Tanah Jahanam.' Through the phenomenon above, the research aims to determine changes in the character of Nyi Misni through the makeup worn by the characters in the film Perempuan Tanah Jahanam. By using qualitative research methods and using a content analysis approach. The results of this study show that the makeup techniques used by the character Nyi Misni in the film Perempuan Tanah Jahanam influence character changes, and three makeup techniques are used. This film features corrective makeup, character makeup, special effects makeup, and prosthetic makeup. The conclusion of this study is the makeup used by the characters who have a significant role in supporting the change in Nyi Misni's character in this film. Moreover, in this film, timeline changes occur during the storyline, so using the right makeup technique is very helpful in showing character changes through the characters' appearance. The author hopes that this research can later be used as a reference for material, especially in the realm of film, in the future. Keywords: film; cosmetology, content analysis, meaning of film